Sperm impairing microbial factor: potential candidate for male contraception - Aditi Chauhan; Deepali Thaper; Vijay Prabha (BMC, 2020)
Abstract Background Despite significant advances in contraceptive options for women, vasectomy and condoms are the only options available for male contraception. Due to this limitation, the burden of contraception resides on the shoulders of females only. Therefore, there is an urgent need to develop a safe, effective and reversible method of contraception for men. Amongst the alternative approaches, microbial derived products are gaining attention of the scientific world to combat unintended pregnancies. Earlier in our laboratory, sperm impairing microbial factor (Sperm immobilization factor) isolated from Staphylococcus aureus has shown excellent contraceptive efficacy in female mice. Keeping this in mind, the present study was carried out to exploit the sperm immobilization factor (SIF) as potential male contraceptive using vas deferens for administration in mouse model. Methods SIF (10, 50, 100 or 200 μg) was inoculated in the lumen of right vas deferens whereas the left vas deferens served as control. The mice were sacrificed at Day 3, 7, 14, 21, 30, 45, 60 and 90 after inoculation and the results in terms of change in body weight, seminal parameters, Tissue somatic indices (TSI), haematological parameters, serum level of testosterone, lipid peroxidation and histology were studied. In order to ratify the SIF induced azoospermia SIF (200 μg) was administered with different doses viz. 100, 200, 300, 400 or 500 μg of SIF binding receptor extracted from mouse spermatozoa. Results The weight profile studies of all the experimental groups showed no significant change in the initial and final body weight. In case of seminal parameters, the results revealed that right vas deferens treated with SIF showed azoospermia and with 200 μg of SIF it persisted up to 90 days. TSI of reproductive organs and non-reproductive organs showed no significant change in all the experimental groups. The haematological indices were found to be unaltered throughout the course of investigation however significant decrease in testosterone level was observed in the treated mice. The treatment also affected the oxidative status of the testis. Further, histological studies revealed hypospermatogenesis and late maturation arrest on treated side whereas the left side which served as control showed normal tissue histology. SIF induced azoospermia was ameliorated when administered with 400 μg of SIF binding receptor from mouse spermatozoa. Conclusion SIF, when administered via intra vas deferens route, could lead to complete azoospermia. Therefore, it could be considered as a potential male contraceptive.